2021
DOI: 10.7150/ijms.53220
|View full text |Cite
|
Sign up to set email alerts
|

Global profile of tRNA-derived small RNAs in gastric cancer patient plasma and identification of tRF-33-P4R8YP9LON4VDP as a new tumor suppressor

Abstract: Transfer RNA (tRNA)-derived small RNAs (tsRNAs) have been found to play important roles in the occurrence and development of cancers. However, the tsRNA profile in gastric cancer is unknown. In this study, we aimed to identify the global tsRNA profile in plasma from gastric cancer patients and elucidate the role of tRF-33-P4R8YP9LON4VDP in gastric cancer. Differentially expressed tsRNAs in the plasma of gastric cancer patients and healthy controls were investigated using RNA sequencing. The expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…Shen detected the expression level of tRF-33-P4R8YP9LON4VDP in 89 gastric cancer patients and 98 healthy plasma samples. The expression level of tRF-33-P4R8YP9LON4VDP in plasma of gastric cancer patients was significantly lower than that of normal people (32). They have verified the potential of tRFs as tumor biomarkers, but they all have limitations and lack of validation of molecular properties and detection methods.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Shen detected the expression level of tRF-33-P4R8YP9LON4VDP in 89 gastric cancer patients and 98 healthy plasma samples. The expression level of tRF-33-P4R8YP9LON4VDP in plasma of gastric cancer patients was significantly lower than that of normal people (32). They have verified the potential of tRFs as tumor biomarkers, but they all have limitations and lack of validation of molecular properties and detection methods.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, through the analysis of the survival curve and the expression level of hsa_tsr016141 in patients with GC patients after operation, we found that hsa_tsr016141 could dynamically monitor the patients with GC after the operation. Several previous studies have highlighted the potential use of tRFs as biomarkers for diagnosing different types of cancer (16,31,32). For example, Mo found that the serum expression level of 5'-tiRNA Val was significantly decreased in 60 breast cancer patients compared with normal controls, suggesting that it may inhibit the progression of breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing revealed tsRNA signatures in cancers, indicating that like microRNAs, tsRNAs may have an oncogenic or tumor-suppressor function in tumors ( 34 , 54 ). In the study of cellular function, it has been found that tRF-33-P4R8YP9LON4VDP could proliferate GC cells in vitro and might be a potential site for targeted therapy ( 55 ). In breast cancer research, it was also found that the runt-related transcription factor 1 (Runx 1) can reverse the excessive proliferation of tumor cells induced by ts-112 ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Shen et al. found that levels of tRF-33-P4R8YP9LON4VDP were significantly downregulated in plasma samples of gastric patients and that this tsRNA inhibited the proliferation of gastric carcinoma cells ( 93 ).…”
Section: Biological Processes Correlated With Tsrnasmentioning
confidence: 99%
“…Thus, these data established a prognostic model for bladder cancer based on the expression levels of specific tsRNA. Recently, researchers have also discovered multiple tsRNA signatures in gastric cancer, papillary thyroid cancer, and other malignancies ( 38 , 91 , 93 ). The literature research on this matter highlighted the need for a broader validation of tsRNAs as sensitive biomarkers for cancer diagnosis and prognosis.…”
Section: Biological Processes Correlated With Tsrnasmentioning
confidence: 99%